Phase transformations in the synthesis of La₀.₇Sr₀.₃MnO₃ nanopowders - Danilenko, I.A.; Konstantinova, T.E.; Shatalova, G.E.; Volkova, G.K.; Doroshkevich, A.S.; Glazunova, V.A. (Functional Materials, 2004)
La₀.₇Sr₀.₃MnO₃ nanopowder has been obtained by co-precipitation of the metal salts out of solution using sodium carbonate. The nanopowder synthesized contains two morphologically different particle types of 40 and 100 to 200 nm size. Using X-ray diffraction and transmission electron microscopy, phase transformations of the synthesis products have been studied within temperature range of 300 to 900°C. The nanoparticle formation genesis is traced and reasons for bimodal size distribution thereof are explained. Нанопорошок La₀.₇Sr₀.₃MnO₃ получен методом совместного осаждения растворов солей металлов карбонатом натрия. Синтезированный нанопорошок состоит из двух типов частиц с размерами 40 и 100-200 нм и разной морфологической формой. Методами рентгеноструктурного анализа и просвечивающей электронной микроскопии исследовались фазовые превращения продуктов синтеза в интервале температур 300-900°С. Прослежен генезис образования наночастиц и объяснены причины их бимодального распределения по размерам. Нанопорошок La₀.₇Sr₀.₃MnO₃ одержано методом сумісного осадження розчинів солей металів карбонатом натрію. Синтезований нанопорошок складається з двох типів частинок із розмірами 40 та 100-200 нм і різною морфологією. Методами рентгеноструктурного аналізу і просвічуючої електронної мікроскопії досліджено фазові перетворення продуктів синтезу в інтервалі температур 300-900°С. Простежено генезис утворення наночастинок і пояснено причини їх бімодального розподілу за розмірами.